Prologue to the Symposium. Holistic vision on integral management during the climacteric - Ayala-Peralta, Félix Dasio (2018)
Strategies in climacteric management have changed in recent years as a result of recent research results in this area, since not only hormonal and non-hormonal therapy are used; Rather, changes in lifestyle, including diet and exercise, can help reduce the symptoms of menopause; other therapeutic measures must be used individually according to the needs of each patient (1). The clinic during the climacteric is variable; However, vasomotor symptoms (SVM) and genitourinary menopause syndrome (GMS) are cardinal symptoms of menopause (1). The topics covered in this symposium deal with aspects of management of climacteric symptomatology, monitoring and therapeutic alternatives. Once the need to initiate menopausal hormone therapy has been determined, in the absence of contraindications, the most appropriate treatment must be determined.